Влияние Пикарескного романа на роман Никоса Казандзакиса о греке Алексисе Зорба - Александрова, О.Н. (Культура народов Причерноморья, 2013)
В статье Александровой О.Н. «Влияние пикарескного романа на роман Никоса
Казандзакиса о греке Алексисе Зорба» роман известного греческого писателя ХХ века Никоса
Казандзакиса рассматривается в контексте развития европейской и греческой литературы Нового
времени, в частности, обнаруживаются параллели с романами Д.Дефо, Дж.Свифта и М.Сервантеса.
Также затрагивается проблема связи и преемственности образов плутов греческой литературы
Нового времени с Древнегреческой литературой. В круг рассматриваемых проблем входят вопросы
возникновения плутовского романа, связь его с античной романистикой и влияния разных его аспектов
на технику создания текста романа Никоса Казандзакиса «Грек Зорба»: проблема перевода названия
романа на русский язык, характеристики персонажей и особенности образа пикаро, своеобразие образа
Алексиса Зорба и т.п. У статті Александрової О.М. «Вплив пікареськного роману на роман Нікоса Казандзакіса
про грека Алексіса Зорба» роман відомого грецького письменника ХХ століття Нікоса Казандзакіса
розглядається в контексті розвитку європейської і грецької літератури Нового часу, зокрема,
виявляються паралелі з романами Д.Дефо, Дж.Свіфта і М. Сервантеса. Також вирішується проблема
зв'язку і наступності образів шахраїв грецької літератури Нового часу з Давньогрецької літературою. У
коло розглянутих проблем входять питання виникнення шахрайського роману, зв'язок його з античною
романістикою та вплив різних аспектів на техніку створення тексту роману Нікоса Казандзакіса «Грек
Зорба»: проблема перекладу назви роману на російську мову, характеристики персонажів і особливості
способу пікаро , своєрідність образу Алексіса Зорба і т.п. The Article by Alexandrova O.N. under the title "The Influence of a picaresque novel on Nikos
Kazantzakis’s novel about Greek Alexis Zorba" examines the main characteristics and traditions of picaresque
novel and their manifestation in the work of the famous Greek writer of the twentieth century: the traditional title
of the novel, the social role of Picaro, the originality of the image of Alexis Zorba, connection of the picaresque
novels with the ancient Greek literature as well as English, German and Spanish literatue of XVII-XVIII
centuries, and the reflection of these phenomena in Kazantzakis’s novel.
We failed to find out specific criticism by both domestic and foreign researches dedicated to the study of the
traditions the of European picaresque novel in the works of Nikos Kazantzakis which highlights the novelty and
relevance of the research.
In the circle of the problems under consideration are the issues of picaresque novel, its connection with the
ancient Romance studies and the influence of different aspects on the technique of creating the text of Nikos
Kazantzakis novel "Zorba, the Greek": the problem of translation the novel’s title into the Russian language, the
characteristics of the characters and the peculiar features of the image of Picaro, etc.
As a result of the analysis of Kazantzakis’s novel it could be concluded that in contrast to the classical Picaro
Zorba is more endowed with positive traits than negative. Thus, at the end of the novel there is no moral
correction of the hero typical of the picaresque novels, although there is some remorse about the crimes and
errors, and the name of Alexis Zorba has become a telling name in Greece and worldwide. It means vitality,
wisdom and boundless energy.